Analysis of the Promethee Method in Providing Recommendations for Fisherman Groups Eligible for Grant Assistance - Anggara, Thetra; Suranti, Dewi; Sartika , Devi (Jurnal Komputer, 2022)
The Kaur District Fisheries Service annually has a grant assistance program for fishermen such as the procurement of facilities and infrastructure. So far, the process of providing assistance is still carried out manually, starting from collecting data on fishermen groups to determining whether grant assistance for fishing groups is feasible or not. Of course, this requires quite a long time and in addition, the process of submitting proposals is still done manually, so there is often a backlog of documents at the Kaur District Fisheries Office. Analysis of the Promethee Method in providing recommendations for fishermen groups who are eligible for grant assistance was made using the Visual Basic .Net programming language (IDE Visual Studio 2010) and SQL Server 2008 database. Based on data from fisherman groups as many as 4 fisherman groups which have been analyzed using the Promethee Method, the results obtained that the Meluang Jaya fishermen group has the highest net flow promethee value compared to the 3 other groups, namely the Meluang Jaya Fishermen Group, it is recommended to receive grant assistance from the Kaur District Fisheries Service. Based on the results of system testing that has been carried out, the functionality of the recommendation application for fishermen groups who are eligible for grant assistance at the Kaur District Fisheries Service has been running as expected.